Relationship between self-discrepancy and worries about penis size in men with body dysmorphic disorder. (June 2016) - Veale, David; Miles, Sarah; Read, Julie; Bramley, Sally; Troglia, Andrea; Carmona, Lina; Fiorito, Chiara; Wells, Hannah; Wylie, Kevan; Muir, Gordon
Highlights: Determining objective, perceived actual, ideal, and should penis size on a nomogram. Discrepancy between perceived and ideal size was correlated with symptoms of BDD. Men with BDD have greater discrepancies compared to controls. Self-discrepancy in penis size may be a helpful target in therapy. Abstract: We explored self-discrepancy in men with body dysmorphic disorder (BDD) concerned about penis size, men without BDD but anxious about penis size, and controls. Men with BDD ( n  = 26) were compared to those with small penis anxiety (SPA; n  = 31) and controls ( n  = 33), objectively (by measuring) and investigating self-discrepancy: actual size, ideal size, and size they felt they should be according to self and other. Most men under-estimated their penis size, with the BDD group showing the greatest discrepancy between perceived and ideal size. The SPA group showed a larger discrepancy than controls. This was replicated for the perceptions of others, suggesting the BDD group internalised the belief that they should have a larger penis size. There was a significant correlation between symptoms of BDD and this discrepancy. This self-actual and self-ideal/self-should discrepancy and the role of comparing could be targeted in therapy.